Minimally invasive transanal surgery is safe after incomplete polypectomy of low risk T1 rectal cancer: a systematic review. (23rd May 2019) - de Jong, G. M.; Hugen, N.
Abstract: Aim: In patients who have undergone a polypectomy of a malignant rectal polyp without histopathological risk factors other than an involved or unclear resection margin, additional local excision is often performed. Evidence to support this approach is lacking. The aim of this systematic review and meta‐analysis was to determine the outcome in terms of local recurrence, disease‐free survival (DFS) and overall survival (OS) of additional local excision following incomplete polypectomy for low risk T1 rectal cancer. Methods: A comprehensive search for published studies was performed. Only studies in which there was incomplete (or ≤ 1 mm) removal of pT1 rectal polyps or in which the resection plane could not be assessed were included. For each included study data on tumour stage, histological factors, surgical technique, local recurrence rate, 5‐year DFS and 5‐year OS were extracted. The PROSPERO registration number is CRD42017062702. Results: A total of 580 studies were retrieved by the search in the MEDLINE database, Embase and the Cochrane Library. After careful appreciation, four studies were included in the analysis, comprising 102 patients of whom the majority had undeterminable (Rx) resection margins. Local excision via transanal endoscopic microsurgery was reported most frequently. Only 1% of patients developed a local recurrence. One study reported 5‐year DFS and 5‐year OS of 96% and 87% respectively. Conclusion: This study supports the use of additional local excision techniques for rectal cancer patients who underwent an incomplete polypectomy for a malignant rectal polyp in the absence of risk factors other than an uncertain resection margin.